National System of Science, Technology and Innovation and the research in the Brazilian university: geopolitical implications - Del Vechio, Angelo [UNESP] (Univ Fed Sao Carlos, 2017)
This article analyses the constitution of the National System of Science, Technology and Innovation in the analytical focus in the geopolitical aspects involved not only in the creation of the system but also the changes that it has undergone in the last four decades. One of the agents of this system, the universities, receives the main attention, highlighting the contradictory path of these institutions in relation to the foundations of the SNCTI, aimed at inserting the country as a regional power, in a context governed by a globalization process conducted by the markets. In this sense, we highlight the pro- cycal role of the Brazilian university in the present time, which makes it unresponsive to the main national issues.
Keywords: Brasil; Geopolitics; National System of Science; Tecnology and Inovation